Climate Change Impacts in Livestock Sector - Rao, G. S. L. H. V. Prasada; Sejian, V. (International Journal of Economic Plants, 2016)
Global warming is real. Sea surface temperature is increasing. Polar ice is melting. Sea level rise is likely. Increase in sea surface temperature across the Indian Ocean may be having significant influence on summer monsoon over India. Global CC is expected to alter temperature, precipitation, atmospheric carbon dioxide levels, and water availability in ways that will affect the productivity of crop and livestock systems. For livestock systems, CC could affect the costs and returns of production by altering the thermal environment of animals thereby affecting animal health, reproduction, and the efficiency by which livestock convert feed into retained products (especially meat and milk). Further, it is predicted that global warming is likely to increase temperature levels and the frequency of extreme temperatures – hotter daily maximums and more frequent or longer heat waves – which could adversely affect livestock production in the warm season. In the present changing climate scenario, there are numerous stresses other than the heat stress which constrain the livestock and have severe consequences on their production. The projected climate change seriously hampers the pasture availability especially during the period of frequent drought in summer. Thus, livestock suffer from drastic nutrition deficiency. Both the quantity and the quality of the available pastures are affected during extreme environmental conditions.